MENYIASATI KETIMPANGAN DI BIDANG ANTARA DUNIA PENDIDIKAN KEJURUAN DAN DUNIA INDUSTRI - ., Asmungi; Kusnanto, Geri (Heuristic, 2016)
The rapid development of CNC machine technology, often makes the inequality ofknowledge between the world of vocational education (SMK) and the world of industry.Along with the development of computer technology is so fast, now born as CNCmachines with the latest generation Mitsubishi-based, Fanuc-based, or GSK-basedoperating system. Meanwhile in the world of education is still using EMCO-based. Noteasy for SMK to follow developments. Financial constraints is one of classic factors.This study tries to deal with this inequality without being affected by financialconstraints, namely by replacing the engine-based laboratory with a simulator-basedlaboratory. To test whether this simulator is able to overcome inequality, then thetreatment of the two groups were paired consisting of teachers and students. By testingthe hypothesis Ho: Î¼1-Î¼2 = 0, and by using a Likert index analysis known that the CNCsimulator is able to replace the actual existence of a CNC machine. It mean thatinequality can be solved immediately.Keywords: inequality, CNC machining , vocational education, CNC simulator